Exploring Lived Narratives: Indonesian SEA Teacher Awardees' English Teaching Challenges in the Philippines - Setianti, Dika; Aziez, Feisal; Hawanti, Santhy (Linguistics and ELT Journal, 2024)
This study investigates the experiences of Indonesian pre-service teachers majoring in English education who participated in the SEA Teacher program, specifically focusing on those assigned to teach English in the Philippines. The primary objective was to identify the challenges these Indonesian SEA Teacher awardees encountered and the strategies they employed to mitigate these challenges, considering the differing statuses of English in Indonesia (as an EFL context) and the Philippines (as an ESL context). The research utilized a g inquiry approach, complemented by semi-structured interviews, to gather qualitative data. The participants comprised four pre-service teachers who successfully completed the SEA Teacher international teaching practice program in 2023, which spanned one month. The findings reveal several challenges faced by the participants, including issues related to self-confidence, language barriers, the educational system, and the availability of facilities. The study underscores the importance of thorough preparation, adaptability, and mentor support in overcoming these obstacles and enhancing teaching practices.